2013
DOI: 10.1007/s13762-013-0446-2
|View full text |Cite
|
Sign up to set email alerts
|

A review on common vegetables and legumes as promising plant-based natural coagulants in water clarification

Abstract: Coagulation and flocculation provide a rather straightforward method towards water clarification. However, ongoing debates over worrying health issues linked to chemical coagulants have paved the way to develop plantbased natural coagulants. Natural coagulants are not only water clarifying agents, but they also have antimicrobial and heavy metal removal properties in some instances. These are highly attractive in the transformation of raw surface water into potable drinking water. A total of 14 plant-based nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
75
0
14

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(103 citation statements)
references
References 80 publications
0
75
0
14
Order By: Relevance
“…Natural polymers are an economically viable alternative to chemical coagulants (Sanghi et al 2006;Choy et al 2015). Natural polymers based on lentil extract have been used as treatment agents to reduce turbidity; however they have not been applied yet in coagulation and flocculation processes in the paper industry.…”
Section: Introductionmentioning
confidence: 99%
“…Natural polymers are an economically viable alternative to chemical coagulants (Sanghi et al 2006;Choy et al 2015). Natural polymers based on lentil extract have been used as treatment agents to reduce turbidity; however they have not been applied yet in coagulation and flocculation processes in the paper industry.…”
Section: Introductionmentioning
confidence: 99%
“…Different trends were observed with both leucaena and papaya (Figures 3b and 3c). At low coagulant dosage, turbidity removal was low due to insufficient coagulating agent (Choy et al, 2015); however, overdosage could lead into colloid The protein in the seeds was the active coagulant agent in this study. It is known that protein is an amphoteric molecule, which is highly influenced by pH; at a pH above its isoelectric point, the protein molecule will have negative surface charge.…”
Section: Effect Of Dosage and Ph On Turbidity Removalmentioning
confidence: 77%
“…The effect of M. oleifera dosage was reported by Pritchard et al (2010); beyond the optimum coagulant dosage, the coagulation effect became less effective, thus constant % removal was obtained (Pritchard et al, 2010). Overdosage of coagulant tends to lead to a colloid restabilization effect (Choy et al, 2015); however, this effect is not observed in M. oleifera (Ndabigengesere et al, 1995). Different trends were observed with both leucaena and papaya (Figures 3b and 3c).…”
Section: Effect Of Dosage and Ph On Turbidity Removalmentioning
confidence: 93%
“…The aluminium dose slightly lowered this value to 6.31. However, all of the suspensions showed pH values that were within the optimum range for CF processes (Choy et al 2015, Gorin et al 2015. (2010) reported the acetylation of Musa paradisiaca L. plantain species.…”
Section: Color and Turbidity Removalmentioning
confidence: 95%